Patient Satisfaction with Medical Tourism: A Review of 460 International Plastic Surgery Patients in Colombia. Issue 12 (December 2020) - Campbell, Alex; Restrepo, Carolina; Navas, Genesis
Abstract : Background: Cosmetic surgery is at the forefront of an exploding medical tourism industry. Patients are able to research options globally through the internet, and increasing numbers are seeking improved service, quality, and value through surgery overseas. Little work has been done to measure the patient experience when traveling for surgery and, to our knowledge, this is the largest study of its kind to examine patient satisfaction with medical tourism. Methods: We retrospectively reviewed patient satisfaction surveys completed by 460 consecutive international patients receiving cosmetic surgery at a private plastic surgery practice in Cartagena, Colombia, between February 2016 and April 2018. Results: Overall patient satisfaction was excellent, with 98.2% responding that they would refer us to friends and family. Patient satisfaction ratings across all other items was also very high (range: 97.1%–100%) for information provided, the surgeon, the staff, facilities, and payment. Conclusions: Excellent patient satisfaction is possible with medical tourism if the patient perceives and receives value through effective results, a pleasant experience, and favorable costs. These successes in plastic surgery medical tourism highlight the potential for significant continued growth in this sector as a whole.